Identification of Escherichia coli and Total Plate Count in Seaweed at BPPMHKP Surabaya II - Nabila, Syafa Putri; Agustina, Eva; Laminem, Laminem; Ferri, M. (Jurnal Biologi Tropis, 2025)
Seaweed is a marine commodity with high economic value and is widely used in the food industry. However, its high water content, cultivation environment conditions, and post-harvest handling make seaweed susceptible to microbial contamination, including Escherichia coli, necessitating quality testing to ensure food safety. Previous studies have focused more on general microbiological quality, without emphasizing the identification of Escherichia coli or the determination of Total Plate Count (TPL) as an indicator of the number of mesophilic aerobic bacteria. To fill this gap, this study was conducted to identify Escherichia coli using qualitative tests. There are two stages of testing: a presumptive test using MMGM media and a confirmatory test using TBX media. While TPL was determined using the duplo dilution method, the pour plate technique, and the plate count. The presumptive test results showed that all seven samples were suspected to be positive for Escherichia coli, but were declared negative in the confirmatory test. Meanwhile, the TPL results showed that two samples exceeded the standard, namely sample D and the Escherichia coli sample.